Genotyping of intermediate and saprophytic leptospira strains isolates from rats, soil and water in Sarawak using box-PCR - Ambra Mera, anak Akang (Universiti Malaysia Sarawak (UNIMAS), 2016)
Leptospirosis is a globally re-emerging disease which can result to morbidity and mortality in both humans and animals. Leptospirosis is not new in Malaysia, yet the information and knowledge on this disease is still inadequate. This study aimed at genotyping intermediate and saprophytic Leptospira strains isolated from soil, water and rats in Sarawak by using BOX-PCR technique and to determine the genetic relatedness among intermediate and saprophytic Leptospira strains respectively. BOXAIR primer was able to produce BOXPCR banding profiles with different fingerprint pattern among each of isolates. A dendrogram was constructed by using Dice coefficient similarity matrix and UPGMA based on fingerprint pattern obtained from the BOX-PCR profile. The phylogenetic analysis using PyElph software has characterized 29 intermediate isolates into 9 major clusters and 5 single isolates with calculated discriminatory index of 0.9434. Meanwhile, for the 41 saprophytic strains, they were clustered into 10 major clusters with 5 single isolates at the calculated discriminatory index of 0.932. The result of this study indicates that BOX-PCR can be used to study the genetic diversity and relatedness among the Leptospira strains based on the source and the location of isolation.